2012
DOI: 10.1017/s0022215112002022
|View full text |Cite
|
Sign up to set email alerts
|

Six years of evidence-based adult dissection tonsillectomy with ultrasonic scalpel, bipolar electrocautery, bipolar radiofrequency or ‘cold steel’ dissection

Abstract: In this adult series, bipolar radiofrequency tonsillectomy was superior to ultrasonic, bipolar electrocautery and cold dissection tonsillectomies. This method combines the advantages of 'hot' and 'cold' tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 20 publications
3
38
1
Order By: Relevance
“…Traditional surgical techniques using the scalpel, guillotine, or snare have largely been replaced with techniques utilizing cautery to limit intraoperative blood loss. However, it has been reported that early post-operative pain may be more intense after the mechanical trauma of cold dissection technique, whereas hot methods may have a higher incidence of late post-operative pain [13]. In a systematic review of Leinbach et al [14] electrodissection caused increased postoperative pain in comparison with cold dissection tonsillectomy.…”
Section: Discussionmentioning
confidence: 98%
“…Traditional surgical techniques using the scalpel, guillotine, or snare have largely been replaced with techniques utilizing cautery to limit intraoperative blood loss. However, it has been reported that early post-operative pain may be more intense after the mechanical trauma of cold dissection technique, whereas hot methods may have a higher incidence of late post-operative pain [13]. In a systematic review of Leinbach et al [14] electrodissection caused increased postoperative pain in comparison with cold dissection tonsillectomy.…”
Section: Discussionmentioning
confidence: 98%
“…Despite decreased operative time, a low rate of postoperative bleeding, and cost‐efficiency associated with these methods, the use of cold dissection has been abandoned at many institutions due to high intraoperative blood loss and perceived perioperative risk when compared to other methods . As a result, monopolar electrocautery gained popularity due to a reported decrease in intraoperative hemorrhage rate and ease of use . However, one study suggested increased postoperative pain secondary to the high continuous thermal energy (400°C to 600°C) used for dissection .…”
Section: Introductionmentioning
confidence: 99%
“…3 As a result, monopolar electrocautery gained popularity due to a reported decrease in intraoperative hemorrhage rate and ease of use. 4 However, one study suggested increased postoperative pain secondary to the high continuous thermal energy (400 C to 600 C) used for dissection. 4 Regarding the rate of postoperative hemorrhage, studies are largely contradictory without clear consensus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…full slough = 0% healing ranging to no slough = 100% healing). 18,20 Other studies utilized the interpretation made by a single clinician's examination finding on designated post-operative days of follow-up (e.g. appointment at day 7 post tonsillectomy).…”
Section: Estimation Of Healed Areamentioning
confidence: 99%